The Effect Of Raw Material Costs And Direct Labor Costs On Production Results (Case Study At Mr. Asep Yaya's Tofu Factory In Sukaratu Tasikmalaya) - Teli Muhamad Adam; Rita Tri Yusnita; Suci Putri Lestari (Journal of Indonesian Management, 2022)
This study aims to determine and analyze the effect of raw material costs and production labor costs partially or simultaneously at the Tofu Factory of Mr. Asep Yaya in Sukaratu Tasikmalaya for the 2019-2021 period. The research method used in this research is to use the causal relationship method (comparative causal) with a quantitative approach. The data used is primary data. The population of this study is the annual financial report of Mr. Asep Yaya's Tofu Factory in Sukaratu Tasikmalaya and the sample was taken for 3 years for the 2019-2021 period. This study uses the analysis method of data normality test, classical assumption test, multiple linear regression test, correlation test, coefficient of determination test, and hypothesis testing. The results of this study indicate that simultaneously the cost of raw materials and labor costs have a significant effect on production results at the Tofu Factory of Mr. Asep Yaya in Sukaratu Tasikmalaya. The cost of raw materials partially has a positive and significant effect on the Production Results of Mr. Asep Yaya's Tofu Factory in Sukaratu Tasikmalaya. Then the Labor Cost partially negative and significant effect on the Production Results of Mr. Asep Yaya's Tofu Factory in Sukaratu Tasikmalaya.